Lung Cancer in Homeless People: Clinical Outcomes and Cost Analysis in a Single Institute. (27th April 2016) - Suh, Koung Jin; Kim, Ki Hwan; Lim, Jin; Park, Jin Hyun; Kim, Jin-Soo; Choi, In Sil
Abstract : Introduction . To characterize the demographic and clinical features, outcomes, and treatment costs of lung cancer in homeless people. Methods . Medical records of 22 homeless patients with lung cancer at Seoul National University Boramae Medical Center in Seoul, South Korea, were retrospectively analyzed. Results . All patients were men (median age, 62 years). Most patients (78%) had advanced disease (stage IIIB, n = 2 ; stage IV, n = 15 ). Seven died during initial hospitalization (median survival, 1.5 months). Six were lost to follow-up after initial outpatient visits or discharges from initial admission (median follow-up, 13 days). Only 4 received appropriate treatment for their disease and survived for 1, 15, 19, and 28 months, respectively. Conversely, 4 of 5 patients with early stage disease (stage I, n = 4 ; stage IIA, n = 1 ) received curative surgery (median follow-up 25.5 months). The median treatment cost based on 29 days of hospitalization and 2 outpatient visits was 12, 513, constituting 47.3% of the 2013 per capita income. Inpatient treatment accounted for 90% of the total costs. The National Health Insurance Service paid 82% of the costs. Conclusion . Among the homeless, lung cancer seems to be associated with poor prognosis and substantial costs during a relatively short follow-up and survival period.